High Precision Spatial Positioning. Issue 2 (April 2015) - Schulze, Birgit
Abstract Today, computed tomography (CT) is an established method with synchrotron radiation sources to obtain volume information from numerous sample types at micrometer resolution. However, it is a fact that the examination of extended flat microsystems or planar test objects is often unsatisfactory when the sample is considerably larger than the area of interest for examination. The considerable variation in X‐ray transmission during a scan often creates artefacts during reconstruction. This limitation was overcome by introducing a new imaging method which now enables calculating threedimensional representations of flat, widely extended objects. However, to obtain meaningful raw data, the sample and the detector need to be positioned with high precision and stability. This demanding task was solved by employing a positioning system specifically developed for this task.